1C.08: THE INTER-ARM DIFFERENCE IN BLOOD PRESSURE AND MORTALITY. (June 2015) - Clark, C.; Shore, A.; Taylor, R.; Campbell, J.
Abstract : Objective: We previously reported the association of inter-arm differences in blood pressure measurements (IAD) with increased cardiovascular and all-cause mortality. Several new large cohorts have been reported since our 2012 meta-analysis. We have therefore updated our meta-analyses to take account of these new data. Design and method: Systematic review and meta-analysis: Medline, Embase and CINAHL were searched for studies reporting survival data in association with IAD. Study level hazard ratios (HR) were extracted for systolic IADs >=10mmHg and >=15mmHg, and pooled using generic inverse variance in a random effects model. Statistical heterogeneity was assessed using the I 2 statistic. Results: Searches to 12th November 2014 identified 3514 unique citations. Eighty full texts were assessed, and 13 studies (reporting data for 14 unique cohorts) contributed to the analyses, Median follow up ranged from 3 to 13 years. Five cohorts employed a simultaneous method of IAD measurement; the remainder used sequential measurements. Ten cohorts were recruited from community populations, including one hypertensive and one diabetic cohort. Four were selected hospital cohorts at increased vascular risk. Cardiovascular mortality was greater with an IAD >=10mmHg (HR 1.9 (95%CI 1.3 to 2.6; 7 cohorts, 13815 participants; I 2  = 45%) and an IAD >=15mmHg (HR 1.7 (1.2 to 2.4; 9 cohorts; 18241 participants; I 2  = 30%). For all-cause mortality HRs were 1.4 (1.2 to 1.8; 10 cohorts, 17709 participants; I 2  = 62%) for IAD >=10mmHg and 1.4 (1.1 to 1.7; 12 cohorts, 18714 participants; I 2  = 46%) for IAD >=15mmHg. Heterogeneity between studies could be accounted for by stratification according to underlying population cardiovascular risk, with higher HRs seen in populations at elevated risk; cardiovascular mortality with an IAD >=10mmHg: HR 1.4 (1.1 to 1.8; I 2  = 0%) for community based cohorts compared to 3.8 (2.2 to 6.6; I 2  = 0%) for those at elevated cardiovascular risk (p = 0.001; Figure). Figure. No caption available. Conclusions: New studies confirming the association of an IAD with increased cardiovascular and all-cause mortality are consistent with previously published findings. Risks associated with an IAD rise in association with the underlying vascular risk of the population studied.